2005
DOI: 10.1007/s10461-005-9009-y
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Patterns of Highly Active Antiretroviral Therapy (HAART) Adherence

Abstract: Strict adherence to highly active antiretroviral therapy (HAART) is necessary for successful suppression of HIV replication. A large number of individuals are not adherent, however, and the reasons for non-adherence are varied and complex. We utilized cluster analyses to identify subgroups of adherers in a sample of 222 HIV positive individuals whose HAART use was electronically monitored. Five distinct subgroups were identified, with characteristic variations across the week and over the course of the 4-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 15 publications
3
45
1
Order By: Relevance
“…These findings were similar to those of studies [6,7] conducted in resourcelimited settings. Adherence, injecting drug use, and baseline pVL were associated with time to viral load suppression in multivariate analysis; these observations have also been previously reported [6,[8][9][10][11][12][13]. These data indicate that this regimen should be expected to lead to successful virological suppression in most settings, and, if this is not the case, it may indicate serious flaws with the implementation of antiviral programmes.…”
Section: Discussionsupporting
confidence: 77%
“…These findings were similar to those of studies [6,7] conducted in resourcelimited settings. Adherence, injecting drug use, and baseline pVL were associated with time to viral load suppression in multivariate analysis; these observations have also been previously reported [6,[8][9][10][11][12][13]. These data indicate that this regimen should be expected to lead to successful virological suppression in most settings, and, if this is not the case, it may indicate serious flaws with the implementation of antiviral programmes.…”
Section: Discussionsupporting
confidence: 77%
“…13,1619 Although the current cognitive impairment-profile of HIV is relatively mild for many individuals, it is nonetheless predictive of significant decline in daily functioning. 20 Also, significant variability in HAART adherence patterns among HIV+ individuals 21 may account for recent reports of variable neurocognitive expression of HIV. 15 …”
mentioning
confidence: 99%
“…It was also noted that the subgroup with a higher degree of cognitive impairment had a consistent drop in the adherence level. These results suggest that there are distinct subgroups of adherers with different behavioral features and interventions are to be designed accordingly to accommodate this variability in behavior [24]. Johnson et al studied the effect of CBT on adherence in 204 HIV-infected patients with self-reported adherence < 85% at baseline and followed them up for up to 25 months.…”
Section: Discussionmentioning
confidence: 99%